Analysis of Gutenberg-Richter b-value and mmax Part II: Estimators for b-value - Haarala Orosco, Mika (2016)
Este artículo es el segundo de una serie de tres, que tienen como objetivo principal obtener un método para calcular los parámetros b y max m que son fundamentales cuando se utiliza la ley de Gutenberg – Richter para la estimación de la peligrosidad sísmica. En este trabajo en particular, nos enfocamos al análisis de estimadores del valor b. Proponemos un estimador para el valor esperado de N M y una expresión exacta y numéricamente estable para su varianza; N M representa los valores ordenados de las magnitudes del catálogo sísmico. Continuamos con el desarrollo de la teoría de las funciones de Kijko-Sellevoll, aplicándolas al cálculo de estimadores de b generales. This report is the second of a series of three which have the main goal to achieve a method to estimate the parameters b and max m that are essential when Gutenberg-Richter law is used for seismic hazard assessment. This paper is devoted to analyze the estimators of b-value. We give an estimator for the expected value of N M and an exact and numerically stable variance for it; N M represents the ordered values (by size) of magnitude catalogue. We go on the development of the theory of Kijko-Sellevoll functions, applying them to calculate generalized b estimators of the seismic catalogue.